Quality of life beyond diagnosis in intellectual disability – Latent profiling. (October 2022) - Leonard, Helen; Whitehouse, Andrew; Jacoby, Peter; Benke, Tim; Demarest, Scott; Saldaris, Jacinta; Wong, Kingsley; Reddihough, Dinah; Williams, Katrina; Downs, Jenny
Abstract: Objective: To compare quality of life (QOL) across diagnoses associated with intellectual disability, construct QOL profiles and evaluate membership by diagnostic group, function and comorbidities. Method: Primary caregivers of 526 children with intellectual disability (age 5–18 years) and a diagnosis of cerebral palsy, autism spectrum disorder, Down syndrome, CDKL5 deficiency disorder or Rett syndrome completed the Quality of Life Inventory-Disability (QI-Disability) questionnaire. Latent profile analysis of the QI-Disability domain scores was conducted. Results: The mean (SD) total QOL score was 67.8 (13.4), ranging from 60.3 (14.6) for CDD to 77.5 (11.7) for Down syndrome. Three classes describing domain scores were identified: Class 1 was characterised by higher domain scores overall but poorer negative emotions scores; Class 2 by average to high scores for most domains but low independence scores; and Class 3 was characterised by low positive emotions, social interaction, and leisure and the outdoors scores, and extremely low independence scores. The majority of individuals with autism spectrum disorder and Down syndrome belonged to Class 1 and the majority with CDKL5 deficiency disorder belonged to Class 3. Those with better functional abilities (verbal communication and independent walking were predominately members of Class 1 and those with frequent seizures were more often members of Class 2 and 3. Conclusion: The profiles illustrated variation in QOL across a diverse group of children. QOL evaluations illustrate areas where interventions could improve QOL and provide advice to families as to where efforts may be best directed. Highlights: Three latent profiles of quality of life in intellectual disability were identified. Class membership was influenced by diagnostic group, function, and comorbidities. Profiles could illustrate areas where interventions and supports may be best directed.